Pengaruh Sudut Putar Telur Terhadap Performa Telur Tetas Itik Cihateup - Mawaddah, Siti; Ayuningtyas, Gilang; Gunawan, Libbi Azhafif; Pratama, Aditya; Khalijah, Rizkika; Ramadhani, Adithya; Nurullita, Dinni; Sekar, Ajeng Dzakira; Margareth, Sandra Resta; Jatmiko, Mahardika Rais (Universitas Islam Negeri Alauddin Makassar, 2025)
One way to reduce hatching failure is to set the correct angle of egg rotation during incubation in the incubator. This study is conducted to investigate the effects of a 90° egg turning angle (automatic) and 180° (manual) on fertility, hatchability, mortality, and hatch weight of Cihateup duck eggs. The research activities were conducted at the hatching laboratory of the Vocational School, IPB University, using 70 duck eggs divided into two treatments: P1 (automatic turning with a 90° rotation angle) and P2 (manual turning with a 180° rotation angle). Data analysis was performed using T-test to identify differences between two treatments.The results showed no significant differences in fertility and hatch weight between the two treatments (P>0.05). This may be the management of incubation parameters including temperature, humidity, and egg turning angle settings did not affect these two factors. However, hatchability and mortality showed significant differences (P<0,05). The manual 180° turning treatment produced higher hatchability (52,38%) and lower mortality (47,62%) compared to the automatic 90° turning with hatchability of 21,43% and mortality of 78,57%. These results indicate that a turning angle of 180° is more optimal in supporting embryo development and increasing the success rate of hatching Cihateup duck eggs. It is recommended to use a 180° egg turning angle in incubators to improve the hatching performance of Cihateup ducks.